Tuning the interlayer of transition metal oxides for electrochemical energy storage. Issue 1 (3rd October 2016) - Augustyn, Veronica
Abstract: Abstract : Layered transition metal oxides are some of the most important materials for high energy and power density electrochemical energy storage, such as batteries and electrochemical capacitors. These oxides can efficiently store charge via intercalation of ions into the interlayer vacant sites of the bulk material. The interlayer can be tuned to modify the electrochemical environment of the intercalating species to allow improved interfacial charge transfer and/or solid-state diffusion. The ability to fine-tune the solid-state environment for energy storage is highly beneficial for the design of layered oxides for specific mechanisms, including multivalent ion intercalation. This review focuses on the benefits as well as the methods for interlayer modification of layered oxides, which include the presence of structural water, solvent cointercalation and exchange, cation exchange, polymers, and small molecules, exfoliation, and exfoliated heterostructures. These methods are an important design tool for further development of layered oxides for electrochemical energy storage applications.